Material dignity - Jonasson Lindqvist, Julina (My University, 2022)
This thesis is exploring the definition of material dignity. How architects can ensure what is the most worthy and respectful way of treating a material. The aim of this thesis is to investigate if architects can become more aware in our material and product decisions when designing, by using storytelling as an alternative method of analysing data. The purpose of trying out storytelling as a method is to see if it can help us challenge our perception. Storytelling has the power to highlight larger societal problems that otherwise might be concealed, by forcing yourself to put yourself in the shoes of the material. The act of narrating can therefore be considered a highly effective transformative power, to make us question what good and bad choices are, and to think about cause and effect. This makes us question things we otherwise just accept. The thesis explores a single-use, non-biodegradable plastic bottle that probably all people are familiar with, to uncover and see if it is possible to change one’s perception about the material and getting a deeper understanding on how to draw your own conclusions on how to make conscious material choices. The storytelling method turned out to be a good way of analysing data and challenging one’s perception of a material. However, the method proved very time consuming and perhaps too complex, which means it might not be an appropriate method for architects to use, but more so in research purposes and in school projects to compile and analyse more complex facts and correlations. What one needs to consider to ensure material dignity is to not make assumptions on why and how we use the materials we use and to instead question those assumptions. To recognise that we as architects are the ones that decide its worth, and that it is our responsibility as designers to make decisions that ensure material dignity.